The Implementation of Project for Strengthening the Profile of Pancasila Students in the Independent Curriculum for Elementary School Students - Susanti, Atika; Darmansyah, Ady; Tyas, Deahayu Ning; Hidayat, Rahmat; Syahputri, Devia Okta; Wulandari, Siti; Rahmasari, Annisa (Universitas Muhammadiyah Mataram, 2023)
The Ministry of Education and Culture has introduced the P5 (Strengthening the Pancasila Student Profile) Project as part of the independent curriculum, aimed at developing students' character and behavior in alignment with Pancasila principles. This study aims to describe the implementation of project for strengthening the profile of Pancasila students in the independent curriculum for elementary school students. The research method used is descriptive qualitative research method. The research involved teachers and fourth-grade students as informants. The findings revealed that the P5 project encompassed various programs, including: (1) religious dimension, through congregational Duha prayers, tadarus (Quran recitation), memorizing short surahs, and Friday rituals; (2) independent dimension, through classroom activities, communal handwashing, and toothbrushing; (3) gotong royong dimension, through collaborative activities on Saturdays and cooperation among parents, students, and teachers during exhibitions; (4) global diversity dimension, through Monday ceremonies, holiday commemorations, and activities introducing Bengkulu's traditional food involving parents and teachers; (5) critical reasoning dimension, through ongoing learning processes and waste management activities; and 6) creative dimension, realized through the